Exploring Opportunities and Challenges in the Tempeh Business to Remain Existent and Develop - Dina Ariyanti; Halimatun Saddiah Siregar; Risky Pratama Sianipar (Young Journal of Social Sciences and Humanities, 2025)
The tempehbusiness is one of the micro and small business sectors with great potential in Indonesia 's economy. Tempeh, as a traditional Indonesian fermented soybean product, is increasingly popular both domestically and internationally due to its high nutritional value and affordable price. However, amidst changing times and increasingly tight market competition, many producers face challenges such as the rising price of imported soybeans, limited capital, and shifting consumer behavior driven by modern lifestyle trends. This article explores the opportunities and challenges of the tempehbusiness to ensure its sustainability and growth in the modern era. Based on recent news analysis, it was found that product innovation, including flavored variants and practical packaging, the use of digital technology for marketing, and improvements in production quality and hygiene, are key factors to maintain the sustainability of tempehenterprises in Indonesia. Moreover, government support through training, access to affordable capital, and market access assistance also plays an important role in keeping the business competitive in both domestic and international markets. With these strategic steps, the tempehbusiness can continue to grow and become an important part of Indonesia's cultural and economic heritage. Keywords: , product innovation